2010
DOI: 10.1099/jmm.0.020511-0
|View full text |Cite
|
Sign up to set email alerts
|

Human bovine tuberculosis – remains in the differential

Abstract: Mycobacterium bovis is a pathogen of cattle. The unpasteurized milk of affected cattle is a source of infection in humans. Despite the screening of cattle and the pasteurization of milk, M bovis has not been eradicated. A high index of clinical suspicion is needed in symptomatic patients with a history of possible exposure. At risk groups include animal workers, farmers, meat packers, vets and zoo keepers. Humans are usually infected by the aerosol route. We present two cases of human bovine tuberculosis. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 10 publications
0
16
0
5
Order By: Relevance
“…Although the fulanis usually treat their animals with antimicrobial to reduce the level of infection in the herd, this was not effective probably because the antimicrobials employed were not effective against M. bovis which further confirmed that mycobacterium bovis is resistant to many antibiotics (Bilal et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the fulanis usually treat their animals with antimicrobial to reduce the level of infection in the herd, this was not effective probably because the antimicrobials employed were not effective against M. bovis which further confirmed that mycobacterium bovis is resistant to many antibiotics (Bilal et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Since people who attend to these animals such as herdsmen and veterinarians as well as the general public who consume fresh milk or infected meat are exposed to bovine TB from cattle (Bilal et al, 2010). There is therefore the need to ascertain the burden of BTB in cattle and in human in Ghana using the field approach, rather than abattoir and hospital based approaches targeting herdsmen in rural settings.…”
Section: Tuberculosis (Tb) Is An Infectious Disease Of Warm-blooded Amentioning
confidence: 99%
“…It is caused by Mycobacterium bovis (M. bovis) and is one of the endemic diseases that generate major challenges to government authorities, medical and veterinary professionals, as well as agribusiness value-chains (SKUCE et al, 2012;OIE, 2015). Bovine tuberculosis poses a threat to public health, especially through human consumption of milk and dairy products, as well as by exposure to the aerosols of infected animals (BILAL et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, infection with bTB occurs through ingestion or inhalation of contaminated milk and milk products, contaminated meat and meat products and infected aerosols (Bilal et al, 2010;Danbirni et al, 2017). Studies have shown that a large proportion of humans (82%) and cattle (85%) population in African countries live in agric-economic zones where bTB is endemic or inadequately controlled (Ayele et al, 2004).…”
Section: Introductionmentioning
confidence: 99%